Multi-level Car Parking as a Viable Solution to Traffic Issues in Davao City - Co, Zosimo; Polinar, Mark Anthony N.; Payao, Ronald B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The development of the economy must be strategically reflected in the transportation infrastructure. Traffic issues will arise as the econ-omy expands, which will impede that expansion. Even if the govern-ment does its part to solve the issue, citizens still have problems. The study investigated how Davao City residents perceived current traf-fic-related issues and their detrimental effects. The study used a quan-titative approach with a descriptive research methodology. The study selected 75 residents of Davao City who have encountered traffic is-sues using purposive sampling. Frequency distribution and percent-ages were used to assess the data that had been gathered. The results indicated that unlawful parking of vehicles and high volumes of vehicles on the road were ranked first and second on the list of existing prob-lems; in the same way, delay and time wastage were the respondents’ dominant adverse effects. Thus, the study concludes that multi-level car parking must be added as a strategic solution to the ongoing prob-lem. Moreover, the researchers suggest a multi-level car parking plan considering all vital parts that help potential and existin